FOSTERING EFL STUDENTS' ORAL COMMUNICATION SKILLS THROUGH INDIVIDUAL PRESENTATION - Nurhidayah, Rafika; Aflah, Mita Nur (Edukasi: Jurnal Pendidikan, 2024)
This classroom action research aims to foster the EFL students’ oral communication skills in the English and English literature program in a presentation skills class through an individual presentation project. This research was conducted at the Sekolah Tinggi Bahasa Asing (STBA) Pontianak, whose participants were taken from the fourth-semester students. This research was carried out in three cycles using observation checklists and field notes to collect the data. Afterward, the data were explained quantitatively and qualitatively. The findings show that individual presentation concretely fosters the students’ oral communication skills in the third cycle. The fostering is proven by improving individual presentation aspects such as clarity, sound volume, body position and eye contact, pause, and listener’s attention. Moreover, the fostering is indicated by the changing of the scoring scale from need improvement to good. Hopefully, this research can contribute to advancing research in oral communication skills.